Marketing Communications Strategy in Advanced and Emerging Markets: An International Comparison - Knight, Gary; Fletcher, Richard (Journal of Comparative International Management, 2022)
We examine the role of ‘marketing communications’ in emerging markets. We sought to understand if ‘marketing communications’ holds the same relevance and meanings to managers in emerging markets as to those in advanced economies. Initially we conducted a series of case studies with managers in Vietnam, to evaluate the applicability of marketing approaches in emerging markets and understand the nature of relevant constructs and relationships. We then conducted a second study to deepen knowledge on ‘marketing communications’ in the two types of economies. Initially we developed a collection of hypotheses based on the earlier case study findings and on extant literature. We then utilized large-scale empirical data collected from exporting firms to assess the hypotheses and compare the role of ‘marketing communications’ across emerging markets and advanced economies. Findings confirm the applicability and importance of ‘marketing communications’ in emerging markets and generally show support for the hypotheses. We offer discussion and implications for managers.